Multi-objective non-simultaneous dynamic optimal control for an ejector expansion heat pump with thermal storages. (5th March 2020) - Liu, Fang; Qiu, Wenyu; Deng, Jiaxin; Mo, Qiu; Groll, Eckhard A.; Zhao, Jun; Liang, Juncui
Highlights: Dynamic modeling of an ejector expansion heat pump coupled with thermal storages. Multi-objective non-simultaneous dynamic optimal control for an ejector HPTES. Transient performance parameters of HPTES system used as optimal multi- objectives. Charging performance of thermal storages using heat pump enhanced by an ejector. Mechanisms for charging time reduction and energy savings of HPTES system. Abstract: This study is to enhance the overall performances of a transcritical CO2 heat pump coupled with hot and cold thermal energy storages (HPTES) during energy charging by using a controllable ejector to replace an expansion valve (ExV) in heat pump and a new multi-objective non-simultaneous dynamic optimization strategy. A Modelica-based dynamic simulation model was developed and validated for an ejector expansion CO2 heat pump with thermal storages during charging process, and a model-based multi-objective non-simultaneous dynamic optimization strategy was proposed. Under a single-objective dynamic optimal control strategy, the overall coefficient of performance (COP) can be increased 22.0%, energy consumption can be reduced 17.3%, and charging time can be reduced significantly during charging process of thermal storages by using an ejector expansion heat pump compared to an ExV heat pump. Charging performances of the ejector HPTES system can be enhanced further by using a multi-objective non-simultaneous dynamic optimal control strategy, in which multiple transient performance parameters of the HPTES system, instead of energy consumption and cost as in the literature, were used as multi-objective functions. The mechanisms of dynamic performance enhancements of an ejector HPTES were revealed. This study would be useful for a dynamic optimal control of other coupled energy systems under unsteady conditions.